Orientation of religiosity and radicalism: the dynamic of an ex-terrorist’s religiosity - Sekar Ayu Aryani (Indonesian Journal of Islam and Muslim Societies, 2020)
Recognition of the religious motives and orientations of acts of radicalism and terrorism is often preached by mass media. The religious motive in the context of Islamic radicalism is often referred to the term of jihad, it is the act of seeking Allah's blessings or Lillahi ta'ala. The motive or religious orientation in the view of Religious Psychology is called an intrinsic religious orientation, turning religion a goal of action because of religion itself. This is distinguished from the extrinsic religious orientation that makes religion as a tool for obtaining subjective goals. We aim to understand to what extent the consistency of recognition is viewed from the perspective of religious orientation theory. This is because there is often an inconsistency between claimed motives with attitude. To examine more deeply on this issue, we raised the case of the dynamics of the religious orientation of a former terrorist, Yusuf Adirama, who experienced the dynamics and religious orientation changes of a radical and terrorist into a moderate one. This research reveals that in the case of Yusuf Adirama, the meaning of jihad could change over time following his life experience. Jihad, originally interpreted as taking up arms against the enemies of God, has turned into opposing various acts of violence and helping the needy (Dhuafa) who need help, including those caused by terrorism, both for the perpetrator and victim.